On Theoretical Study of Zagreb Indices and Zagreb Polynomials of Water-Soluble Perylenediimide-Cored Dendrimers - Iqbal, Zahid; Aamir, Muhammad; Ishaq, Muhammad; Shabri, Ani (Journal of Informatics and Mathematical Sciences, 2018)
The topological indices are numerical invariants associated to a graph which describe its molecular topology. In QSAR/QSPR study, the Zagreb indices and Zagreb polynomials are used to predict the bioactivity of different chemical compounds. They also correlate the certain physicochemical properties of the chemical compounds. In this paper, we compute the closed formulas of the first and second Zagreb indices and their variants and their Zagreb polynomials for the two classes of perylenediimide-cored (PDI-cored) dendrimers.